Sustained ventricular fusion simulating a biventricular pacing - VINCENZO CARBONE; VINCENZO MARAFIOTI; MARIA PIA CALABRO'; GIUSEPPE ORETO (International Journal of Cardiovascular Practice, 2017)
An electrocardiogram from a patient implanted with a dual-chamber DDD pacemaker showed paced QRS complexes whose morphology and frontal-plane axis were consistent with biventricular stimulation with right ventricular lead located at the apex. However, some electrocardiographic findings were suggestive, rather, of univentricular right apical pacing and sustained ventricular fusion with competing native atrioventricular conduction in the presence of patient’s spontaneous QRS showing right bundle branch block plus left anterior hemiblock. Shortening atrioventricular delay with magnet application advanced right ventricle stimulation and prevented the supraventricular impulse to contribute to ventricular depolarization, thereby making clear the mechanism of right ventricular apical pacing.